2020
DOI: 10.2147/clep.s246352
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology of Human Adenoviruses: A 20-Year Retrospective Observational Study in Hospitalized Patients in Bern, Switzerland</p>

Abstract: Background: Human adenovirus (HAdV) is an important pathogen seen in clinical practice. Long-term studies may help better understand epidemiological trends and changes in circulating genotypes over time.Purpose: Using a large biobank of samples from hospitalized, adenovirus-positive patients over a 20-year period, we aimed to analyze long-term epidemiological trends and genotypic relatedness among circulating HAdV strains. Methods: Based on samples from hospitalized patients confirmed to be HAdV positive in Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 52 publications
2
47
1
Order By: Relevance
“…The present study recorded the epidemiological distribution of circulating HAdV strains among hospitalized patients with respiratory tract infections (RTIs) between 2017 and 2019 in Guangzhou City, China. In this study, the overall positive rate of HAdV was 2.4%, which is consistent with the positive rate (2.0%-6.1%) found in hospitalized patients with acute viral respiratory infection in other recent reports [3,[19][20][21]. However, two previous studies conducted in the Northern part of China showed a higher HAdV prevalence (10.4%-20.1%) than our study [22,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study recorded the epidemiological distribution of circulating HAdV strains among hospitalized patients with respiratory tract infections (RTIs) between 2017 and 2019 in Guangzhou City, China. In this study, the overall positive rate of HAdV was 2.4%, which is consistent with the positive rate (2.0%-6.1%) found in hospitalized patients with acute viral respiratory infection in other recent reports [3,[19][20][21]. However, two previous studies conducted in the Northern part of China showed a higher HAdV prevalence (10.4%-20.1%) than our study [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…But it was not consistent with that of studies conducted in Northern China [22] and Mexico [29]. In Tanzania and Switzerland, HAdV infections were observed during all seasons of the year with no clear seasonality demonstrated [21,27]. These difference in HAdV prevalence between seasons are interesting and bear future study as seasonal risk could in uence future employment of HAdV vaccines which are in development in China [30].…”
Section: Discussioncontrasting
confidence: 56%
“…But it was not consistent with that of studies conducted in Northern China [ 21 ] and Mexico [ 26 ]. In Tanzania and Switzerland, HAdV infections were observed during all seasons of the year with no clear seasonality demonstrated [ 19 , 27 ]. These difference in HAdV prevalence between seasons are interesting and bear future study as seasonal risk could influence future employment of HAdV vaccines which are in development in China [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human adenovirus (HAdV) is associated with a wide range of illnesses, ranging from common cold to more serious conditions—including serious acute respiratory infections, gastroenteritis, conjunctivitis, haemorrhagic cystitis or meningoencephalitis, which are often underreported ( 68 ). Its paramount role as an agent of RTIs is especially pertinent for children between 1 and 5 years of age ( 69 , 70 ), primarily due to their immature immune system ( 71 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%